Research on Dynamic Modeling Algorithm of College Students' Learning Motivation Factors based on SPSS and Artificial Intelligence Testing Machine - Yang, Suyun (International Conference on Inventive Computation Technologies (Online), 2022)
Research on the dynamic modeling algorithm of college students' learning motivation factors based on SPSS and artificial intelligence testing machine is conducted in this paper. In the designed statistical model, according to the results of the two-sample ANOVA, that is, whether the population variances of the two samples are equal, the t-test of the assumptions of equal variance and heteroscedasticity is selected to infer whether the population means of the two samples are equal. It reflects the variation degree of another variable after controlling the value of one variable. When both variables are normal continuous variables and there is a linear relationship between them on the scatter diagram, it can be considered that there is a linear correlation trend between them. With this designed novel model, the SPSS and artificial intelligence testing machine is designed. Through the various testing, the general performance is validated.